(untitled) (Scientific journal of the Fergana State University, 2024)
As a result of the change in climatic factors, the Fergana Valley, including the South Fergana Valley, has a huge impact on the water regime of the rivers. All rivers in the Southern Fergana mountains are saturated with high mountain waters and snow water. As a result of climate change, the water regime in these rivers also changes, and as a result of the melting of glaciers, the water of rivers increases. But, we can observe that the water regime of rivers starting from the mountains in Northern Fergana is affected by ham and the water of Rivers is decreasing.